Prototyping Power Electronics Systems with Zynq-Based Boards Using Matlab/Simulink—A Complete Methodology - Caseiro, Luís Miguel Antunes (2022)
Many advanced power electronics control techniques present a steep computational load, demanding advanced controllers, such as FPGAs. However, FPGA development is a daunting and time-consuming task, inaccessible to most users. This paper proposes a complete methodology for prototyping power electronics with Xilinx Zynq-based boards using Matlab/Simulink and HDL Coder. Even though these tools are relatively well documented, and several works in the literature have used them, a methodology for developing power electronics systems with them has never been proposed. This paper aims to address that, by proposing a complete programming and design methodology for Zynq-based power electronics and discussing important drawbacks and hurdles in Simulink/HDL Coder development, as well as their possible solutions. In addition, techniques for the implementation of all required peripherals (ADCs, digital outputs, etc.), system protections, and real-time data acquisition on Zynq boards are presented. This methodology considerably reduces the development time and effort of power electronics solutions using Zynq-based boards. In addition, a demonstration Simulink model is provided with all proposed techniques and protections, for use with a readily available development board (Zedboard) and ADC modules. This should further reduce the learning curve and development effort of this type of solution, contributing to a broader access to high-performance control prototyping using Zynq-based platforms. An application example is presented to demonstrate the potential of the proposed workflow, using a Zedboard to control a multilevel UPS inverter prototype with Model Predictive Control.